(untitled) (Indonesian Tax Justice Review, 2024)
The international tax reform agenda led by the OECD’s Base Erosion and Profit Shifting (BEPS) project has reshaped domestic tax systems worldwide, yet its implications for tax justice in developing countries remain contested. This paper examines Indonesia’s post-BEPS reform experience to assess whether global standards advance equitable taxing rights for Global South jurisdictions. Using doctrinal legal analysis and comparative policy evaluation, the study analyzes Indonesia’s adoption of transfer pricing rules, country-by-country reporting, and general anti-avoidance measures. The findings indicate that while BEPS-related reforms enhance transparency and administrative capacity, they also reproduce structural asymmetries by prioritizing the interests of capital-exporting states. Indonesia’s constrained policy space illustrates the limits of a one-size-fits-all approach to international tax governance. This paper argues that tax justice must be reconceptualized beyond formal compliance with global standards to incorporate development needs, institutional capacity, and historical inequality. The global contribution of this study lies in offering empirical and normative insights from a major emerging economy, highlighting the necessity of rebalancing international tax norms to ensure meaningful participation and fair revenue allocation for developing countries. The Indonesian case thus serves as a critical reference point for ongoing debates on inclusive global tax reform.